Niqab Perspektif Mahasiswi IAIN Surakarta: Pemahaman terhadap Teks dan Praktik Bercadar - Hikmawati, Ari; Muttaqin, Zaenal; Hasan, Moh Abdul Kholiq (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2021)
This paper discussed the motives of wearing niqab among Muslim women. Most of Muslim women wear niqab because of religious motives. However, the development of niqab recently brings up a variety of colours and models. This diversity indicates different motives among Muslim women in wearing niqab. Surveying IAIN Surakarta’s students who wear niqab, this research elaborated the relationship between their motives of wearing niqab and their understanding of Islamic teaching about niqab. The research found that even though the main motive to wear niqab is to observe religious teaching, IAIN Surakarta’s students who wear niqab also consider the practice for safety reasons. They also realize that wearing niqab is not an obligation in Islam and follow schools which consider it as preferable (sunah).